2010
DOI: 10.1017/s0950268810002165
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of rubella in Mexico: seasonality, stochasticity and regional variation

Abstract: SUMMARY The factors underlying the temporal dynamics of rubella outside of Europe and North America are not well known. Here we used 20 years of incidence reports from Mexico to identify variation in seasonal forcing and magnitude of transmission across the country and to explore determinants of inter-annual variability in epidemic magnitude in rubella. We found considerable regional variation in both magnitude of transmission and amplitude of seasonal variation in transmission. Several lines of evidence point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
3
59
1
2
Order By: Relevance
“…1 A and B and Figs. S1 and S2) (15,(22)(23)(24)(25). Similar patterns have been reported in other countries in East Africa, suggesting regional consistency (26).…”
Section: Resultssupporting
confidence: 79%
“…1 A and B and Figs. S1 and S2) (15,(22)(23)(24)(25). Similar patterns have been reported in other countries in East Africa, suggesting regional consistency (26).…”
Section: Resultssupporting
confidence: 79%
“…Seasonality in transmission often play an important role in the dynamics of childhood infections (Ferrari et al, 2008; Schenzle, 1984), and is generally observed for rubella (Metcalf et al, 2011a; Metcalf et al, 2011b). In the absence of detailed data, we chose to model seasonal fluctuations as a trigonometric function ( e.g.…”
Section: Model Frameworkmentioning
confidence: 99%
“…However, given no substantial evidence for large variation in transmission for other countries in the region (Metcalf et al, 2011a; Metcalf et al, 2011b), and evidence for transmission predominantly in school children (Fig. 3b), we set β 2 =0.2.…”
Section: Parameterizing the Modelmentioning
confidence: 99%
“…5 Data on these effects are limited for Vietnam. Studies using TSIR (Time-series SusceptibleInfectious-Recovered) models applied to district-level rubella data from Mexico, 21 found regional variation in the amount of transmission and the extent to which transmission varied seasonally. As shown in Figures 2-3, the amount of transmission influences both the impact of vaccination and the CRS incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous work, 20 the CRS incidence per 100,000 live births was calculated for 5-year age groups (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), 25-29, 30-34, 35-39 and 40-44 years) for each year during 2000-2050, assuming a 65% risk of a child being born with CRS if infection occurs during the first 16 weeks of pregnancy. The CRS incidence per live birth for each year in the model for mothers in each 5 year age group was then multiplied by the estimated number of live births to calculate the number of CRS cases born each year.…”
Section: Calculating the Crs Incidencementioning
confidence: 99%